ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BERMAIN GAME ONLINE - Pratiwi, Erni Dwi (Jurnal Pilar Nusa Mandiri, 2014)
Technology develops and increases rapidly. It becomes a buzz in society, especially among teenagers. The online game is one of the technologies that rapidly growing and increasing in demand. This study analyzes six variables: the trust in online game’s websites, online game’s satisfaction, the enjoyment in playing online games, subjective norms, attitudes toward and intention playing online games. The samples were taken from 196 peoples in various regions cafe in Jakarta. Various factors can be affected in the intention of a person is playing an online game. The analysis showed that the satisfaction of online game does not affect a person in playing the game.